Models for the Sectoring-Arc Routing Problem (SARP) - Nunes, Ana Catarina; Mourão, Maria Cândida (Euro XXIV - 24th European Conference on Operational Research, 2010)
The Sectoring-Arc Routing Problem (SARP) models the activities associated with the streets of large urban areas, such as waste collection. The SARP is defined over a mixed graph. Its aim is to identify a given number of similar sectors (sub-graphs) and to build a set of collecting trips in each sector, such that the total duration of the trips is minimized. Each sector is collected by one vehicle and each of its trips can not exceed a given load. Linear mixed integer programming formulations are presented for the SARP, and computational results over a set of benchmark problems are reported.